Predator-Proofing Avian Nestboxes: A Review of Interventions, Opportunities, and Challenges - Joseph M. Marcus; Adam G. Hart; Anne E. Goodenough (Birds, 2023)
Nestboxes are commonly used to increase the number and quality of nest sites available to birds that usually use tree cavities and are considered an important conservation intervention. Although usually safer than natural cavities, birds nesting in simple, unmodified wooden nestboxes remain at risk of depredation. Accordingly, numerous design and placement modifications have been developed to ‘predator-proof’ nestboxes. These include: (1) adding metal plates around entrance holes to prevent enlargement; (2) affixing wire mesh to side panels; (3) deepening boxes to increase distance to nest cup; (4) creating external entrance ‘tunnels’ or internal wooden ledges; (5) using more robust construction materials; (6) developing photosensitive shutters to exclude nocturnal predators; (7) using baffles to block climbing mammals; and (8) regular replacement and relocation. However, the benefits and costs of these modifications are not always well understood. In this global review, we collate information on predator-proofing avian nestboxes designed for tree cavity-nesting birds to assess the efficacy of techniques for different predators (mammalian, avian, and reptilian) in different contexts. We critique the potential for modifications to have unintended consequences—including increasing nest building effort, altering microclimate, reducing provisioning rate, and elevating ectoparasite and microbial loads—to identify hidden costs. We conclude by highlighting remaining gaps in knowledge and providing guidance on optimal modifications in different contexts.